Etika Tanah Aldo Leopold: Telaah Moral Atas Eksploitasi dan Kewajiban Reklamasi Tambang Batu Bara - Priyaji Agung Pambudi; Suyud Warno Utomo; Soemarno Witoro Soelarno; Noverita Dian Takarina (ECOTAS, 2022)
Various natural phenomena unresolved showing increasingly alarming conditions relating to the fulfillment of the right to life for future generations. Philosophy has a strategic role as an important rationale for determining one's position in dealing with the phenomenon. Deep philosophical grounding determines the flow of thought and solutions are formulated. This paper aims to examine the concept of land ethic by Aldo Leopold to determine a solution to the post-mining rehabilitation. This is a qualitative research uses literature review, desk study, and hermeneutic. Literature review from various sources of journals, articles, books, government reports, and corporate reports with related issues. Based on the results anthropocentrism has dominated the mindset of relevant stakeholders. It can be reflected in the policy product, field action, and the activity plan for the rehabilitation of post-mining land. The principle of utilitarianism very coloring all policies and actions taken. These conditions have sacrificed ecosystem especially land no longer considered as a subject that needs to be managed and maintained the quantity and quality. This process if not promptly corrected will result in deterioration of functions and ecosystems services and lead to instability. If that happens, then echoed sustainable development can never be realized.